PERAN KEPUASAN KONSUMEN DALAM MENENTUKAN PENGARUH KUALITAS PRODUK TERHADAP LOYALITAS KONSUMEN - Alivia Rajab; Liza Nora (JURNAL MUHAMMADIYAH MANAJEMEN BISNIS, 2021)
This study aims to determine how much influence product quality has on consumer loyalty in Holland bakery in Jabodetabek with customer satisfaction as a mediating variable. The method used in this research is an associative quantitative method. The source of this research is using primary data and secondary data. The sample collection technique used was purposive sampling technique, with the number of samples tested was 196 respondents of Holland bakery consumers. The data collection technique is using a questionnaire distributed via Google Form to consumers who live in Jabodetabek. Methods of data analysis in this study using the Structural Equation Model (SEM), using the WarpPLS 7.0 approach. The results of this study indicate that product quality has a significant effect on consumer loyalty and product quality with customer satisfaction as a mediation which has a significant effect on customer loyalty. This means that the customer satisfaction variable is a partial mediation, which can affect directly or indirectly between the variable product quality and consumer loyalty, both with the presence of customer satisfaction as a mediation or not, product quality still affects consumer loyalty.Keywords: Product Quality, Customer Satisfaction, Consumer Loyalty